A 2-h diagnostic protocol to assess patients with chest pain symptoms in the Asia-Pacific region (ASPECT): A prospective observational validation study - Than, M.; Cullen, L.; Reid, Christopher; Lim, S.; Aldous, S.; Ardagh, M.; Peacock, W.; Parsonage, W.; Ho, H.; Ko, H.; Kasliwal, R.; Bansal, M.; et al. (2011)
Background: Patients with chest pain contribute substantially to emergency department attendances, lengthy hospital stay, and inpatient admissions. A reliable, reproducible, and fast process to identify patients presenting with chest pain who have a low short-term risk of a major adverse cardiac event is needed to facilitate early discharge. We aimed to prospectively validate the safety of a predefined 2-h accelerated diagnostic protocol (ADP) to assess patients presenting to the emergency department with chest pain symptoms suggestive of acute coronary syndrome. Methods: This observational study was undertaken in 14 emergency departments in nine countries in the Asia-Pacific region, in patients aged 18 years and older with at least 5 min of chest pain. The ADP included use of a structured pre-test probability scoring method (Thrombolysis in Myocardial Infarction [TIMI] score), electrocardiograph, and point-of-care biomarker panel of troponin, creatine kinase MB, and myoglobin. The primary endpoint was major adverse cardiac events within 30 days after initial presentation (including initial hospital attendance). This trial is registered with the Australia-New Zealand Clinical Trials Registry, number ACTRN12609000283279. Findings: 3582 consecutive patients were recruited and completed 30-day follow-up. 421 (11·8%) patients had a major adverse cardiac event. The ADP classified 352 (9·8%) patients as low risk and potentially suitable for early discharge. A major adverse cardiac event occurred in three (0·9%) of these patients, giving the ADP a sensitivity of 99·3% (95% CI 97·9–99·8), a negative predictive value of 99·1% (97·3–99·8), and a specificity of 11·0% (10·0–12·2).